The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4161/org.24843
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the innervation of the prostate gland

Abstract: The adult prostate gland grows and develops under hormonal control while its physiological functions are controlled by the autonomic nervous system. The prostate gland receives sympathetic input via the hypogastric nerve and parasympathetic input via the pelvic nerve. In addition, the hypogastric and pelvic nerves also provide sensory inputs to the gland. This review provides a summary of the innervation of the adult prostate gland and describes the changes which occur with age and disease. Growth and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 136 publications
1
17
0
Order By: Relevance
“…The prostate is highly innervated ( 33 ), and the nerves are required for formation of the prostate during embryogenesis, maturation during puberty, and maintenance of the adult phenotype ( 34 ). Thus, like androgen stimulation, sympathetic stimuli contribute to prostatic differentiation in vivo ( 35 ).…”
Section: Adrenergic Receptor’s Functional Role In the Prostatementioning
confidence: 99%
See 1 more Smart Citation
“…The prostate is highly innervated ( 33 ), and the nerves are required for formation of the prostate during embryogenesis, maturation during puberty, and maintenance of the adult phenotype ( 34 ). Thus, like androgen stimulation, sympathetic stimuli contribute to prostatic differentiation in vivo ( 35 ).…”
Section: Adrenergic Receptor’s Functional Role In the Prostatementioning
confidence: 99%
“…In normal prostate physiology, the sympathetic nervous system regulates prostate differentiation and secretory activity of luminal cells, predominantly through ADRB2 ( 34 , 35 , 40 , 41 ). We know from in vitro and in vivo prostate cancer models that chronic elevation of ADRB activity by exposing mice to repeated stress or by adding ADRB agonists promotes neuroendocrine differentiation ( 70 , 84 86 ), metastasis ( 58 , 103 ), angiogenesis ( 78 , 81 , 112 , 115 ), and apoptosis-resistance ( 116 , 120 ); together indicating that adrenergic signaling promotes prostate cancer progression (Figure 2 ).…”
Section: Controversies Clinical Implications and Conclusionmentioning
confidence: 99%
“…The prostate growth's anatomical obstruction may be the main reason for lower urinary tract symptoms, but inflammation, infection, and metabolic disorders can also be possible etiologies [76]. The prostate is innervated with the parasympathetic and sympathetic nerves [77]. The cholinergic nerves and muscarinic receptors are present in the fibromuscular stroma of the prostate, which can explain the previous beneficial effects of BoNT-A intraprostatic injection treatments [78][79][80][81].…”
Section: Bont-a Injection For Bphmentioning
confidence: 99%
“…Dense neuropeptide Y innervation is present throughout the prostatic stroma but most studies have not found the neuropeptide to be involved in the contraction of the prostate (White et al, ).…”
Section: Neural Innervation Of the Prostatementioning
confidence: 99%
“…If the pelvic muscles do not contract the semen emission is one of dribbling, powered by the peristaltic contractions of the urethra alone with little ecstatic pleasure (Newman et al, ). Although orgasm normally takes place concomitantly with ejaculation, the two processes are actually independent (Levin, ).While the prostate is involved in forming part of the ejaculate (as detailed above) it is also involved in ejaculation per se as its fibromuscular covering containing smooth muscle contracts clonically under its adrenergic innervation propelling the semen from the prostatic urethra into the penile urethra (White et al, ).…”
Section: Recreative Functionsmentioning
confidence: 99%